Cardioprotective Action of Ginkgo biloba Extract against Sustained β-Adrenergic Stimulation Occurs via Activation of M2/NO Pathway - Mesquita, Thássio R. R.; de Jesus, Itamar C. G.; dos Santos, Jucilene F.; de Almeida, Grace K. M.; de Vasconcelos, Carla M. L.; Guatimosim, Silvia; Macedo, Fabrício N.; dos Santos, Robervan V.; de Menezes-Filho, José E. R.; Miguel-dos-Santos, Rodrigo; Matos, Paulo T. D.; Scalzo, Sérgio; et al. (Frontiers in Pharmacology, 2017)
Ginkgo biloba is the most popular phytotherapic agent used worldwide for treatment of several human disorders. However, the mechanisms involved in the protective actions of Ginkgo biloba on cardiovascular diseases remain poorly elucidated. Taking into account recent studies showing beneficial actions of cholinergic signaling in the heart and the cholinergic hypothesis of Ginkgo biloba-mediated neuroprotection, we aimed to investigate whether Ginkgo biloba extract (GBE) promotes cardioprotection via activation of cholinergic signaling in a model of isoproterenol-induced cardiac hypertrophy. Here, we show that GBE treatment (100 mg/kg/day for 8 days, v.o) reestablished the autonomic imbalance and baroreflex dysfunction caused by chronic β-adrenergic receptor stimulation (β-AR, 4.5 mg/kg/day for 8 days, i.p.). Moreover, GBE prevented the upregulation of muscarinic receptors (M2) and downregulation of β1-AR in isoproterenol treated-hearts. Additionally, we demonstrated that GBE prevents the impaired endothelial nitric oxide synthase (eNOS) activity in the heart. GBE also prevented the pathological cardiac remodeling, electrocardiographic changes and impaired left ventricular contractility that are typical of cardiac hypertrophy. To further investigate the mechanisms involved in GBE cardioprotection in vivo, we performed in vitro studies. By using neonatal cardiomyocyte culture we demonstrated that the antihypertrophic action of GBE was fully abolished by muscarinic receptor antagonist or NOS inhibition. Altogether, our data support the notion that antihypertrophic effect of GBE occurs via activation of M2/NO pathway uncovering a new mechanism involved in the cardioprotective action of Ginkgo biloba.